Impact of irrational antibiotic therapy to hospital cost of care of pneumonia in patients in Dr. Sardjito Hospital - Edi Sutrisno (Faculty of Medicine Universitas Gadjah Mada, 2013)
ABSTRACTBackground: The mortality rate from pneumonia remains very high, reaching 15% in the United States while inIndonesia pneumonia is the second leading cause of death. Antibiotics improve outcomes in those with bacterialpneumonia. Irrational antibiotic therapy impacts to bacteria resistance, potentially increasing side effects of drugs,prolonged patient’s length of stay and higher total hospital costs.Aim: This study aimed to improve the service quality by calculating the percentage of irrational antibiotic therapybased on Gyssens workfl ow and the additional total of consumables antibiotics costs.Methods: The study design was retrospective, including 57 pneumonia inpatients in internal medicine departmentwards in Dr. Sardjito Hospital, from November 2011 to January 2012. Statistical analyses were conducted byusing Mann-Whitney U test.Results: From 57 pneumonia inpatients, irrational antibiotic therapy reached 68,4% (39 of 57 patients).Azithromycin was misused and overused antibiotic. Total excess cost of daily antibiotic were Rp 294,000.00and consumables antibiotics were Rp 215,000.00Conclusion: Irrational antibiotic therapy in pneumonia is associated with and an overall impacts on healthcarecosts.Keywords: irrational antibiotic therapy, health-care cost, and customer satisfaction.